Life history evolution : a biological meta-theory for the social sciences /: a biological meta-theory for the social sciences. (2018) - Hertler, Steven C; Figueredo, Aurelio José; Peñaherrera-Aguirre, Mateo; Fernandes, Heitor B. F; Woodley, Michael A
No abstract available